Evaluación de la satisfacción laboral del personal docente y administrativo en la Unidad Educativa Fiscal 13 de Octubre del Cantón Bolívar - Calderón Ganchozo, Fanny Albaida (2016)
This research work is to evaluate job satisfaction on faculty and staff members in the October 13 Public High School of the city of Calceta in Bolivar Canton, with the purpose of examining the weaknesses that could affect decisions therefore the administration of the institution, and later by the ministry that governs it, which was designed using methods such as: No experimental, field and descriptive method, the same as the characteristics of the phenomenon under study is detailed, where the current situation of the institution is described, it was employed as technical survey in order to know the appreciation of the teaching and administrative staff that provided the information required by using a questionnaire and an interview to collect the necessary data to the execution of the improvement plan. One of the processes with greater influence on decisions to be taken by the human resource management (HRM) in terms of personnel to ensure a proper working environment for better performance of everyday activities. The purpose of the research was to analyze job satisfaction, through a descriptive study with field design, and a population that was represented by the universe of 74 employees. Similarly, actions are recommended to improve working conditions, which benefit workers, consequently the school and the community in general.